TÜRKİYE'DE YETİŞEN FARKLI LOKALİTELERDEN TOPLANMIŞ BAZI CİRSİUM MİLLER TÜRLERİ ÜZERİNDE SİTOTAKSONOMİK BİR ARAŞTIRMA - YÜKSEL, EDA (Fırat Üniveristesi, 2009)
Bu çalışmada, Türkiye'de yetişen farklı lokalitelerden toplanmış bazı Cirsium Miller türlerine ait 5 tür (C. ligulare Boiss., C. bulgaricum DC., C. ciliatum (Murr.) Moench subsp. szovitsii (C. Koch) Petrak, C. ellenbergii Bornm, C. vulgare (Savi) Ten) karyolojik ve sitotaksonomik bakımdan incelenmiştir. İncelenen türler Epitrachys DC. seksiyonunda yer almaktadır.İncelenen 5 türün (C. ligulare, C. bulgaricum, C. ciliatum, C. ellenbergii, C. vulgare) kromozom çalışmaları için tohumlarından yararlanılmıştır. Kromozom çalışmaları sonucunda türlerin somatik kromozomlarının sayım ve ölçümleri yapılmıştır. Beş türden C. ligulare 2n=32 ve 34, C. bulgaricum 2n=32 ve 34, C. ciliatum 2n=34, C. ellenbergii 2n=34, C. vulgare 2n=34 ve 68 bulunmuştur. Bu durumun tespiti cinsin farklı ve aynı türleri arasında aneuploidi ve poliploidinin olabileceğini göstermektedir. İncelenen bu türlerde bütün kromozomlar median noktalı (M), median bölgeli (m) ve submedian (sm) sentromerli bulundu.

In this study, five species belonging to some Cirsium Miller species collected from different localities growing in Turkey (C. ligulare Boiss., C. bulgaricum DC., C. ciliatum (Murr.) Moench subsp. szovitsii (C. Koch) Petrak, C. ellenbergii Bornm C. vulgare (Savi) Ten.) were examined in karyologic and cytotaxonomic aspects. Examined species were placed in Epitrachys DC section. The seeds of investigated five species (C. ligulare, C. bulgaricum, C. ciliatum, C. ellenbergii, C. vulgare) was used for chromosomes analysis. The numbers and measurements of somatic chromosomes were done at the end of chromosomes works. From five species, the chromosome numbers followed as: C. ligulare 2n=32 and 34, C. bulgaricum 2n=32 and 34, C. ciliatum 2n=34, C. ellenbergii 2n=34, C. vulgare 2n=34 and 68. The determination of this situation in the cates the assumption that aneuploidy and polyploidy may exist between the same and the different types of the species. İn these examined types all of the chromosomes were found as median pointed (M), median regioned (m) and submedian (sm) centromered.
A cytotaxonomic investigation on some Cirsium Miller species collected from different localities growing in Turkey
Keywords: Biyoloji